Interventions that cause weight loss and the impact on cardiovascular risk factors: a systematic review and meta‐analysis. (21st June 2016) - Zomer, E.; Gurusamy, K.; Leach, R.; Trimmer, C.; Lobstein, T.; Morris, S.; James, W.P.T.; Finer, N.
Summary: Overweight and obesity increase the risks of diabetes and cardiovascular disease (CVD). This has been shown to be reversed with weight loss. A systematic review and meta‐analysis were performed to determine the effect of weight loss in the primary prevention of CVD. PubMed, Embase and the Cochrane Library databases were searched electronically through to May 2013. Randomized controlled trials assessing weight loss and cardiovascular risk factors and outcomes were included. A random effects meta‐analysis, with sub‐group analyses for degree of weight loss, and age were performed. Because few studies reported clinical outcomes of CVD, analyses were limited to cardiovascular risk factors (83 studies). Interventions that caused any weight loss significantly reduced systolic blood pressure (−2.68 mmHg, 95% CI −3.37, −2.11), diastolic blood pressure (−1.34 mmHg, 95% CI −1.71, −0.97), low‐density lipoprotein cholesterol (−0.20 mmol L −1, 95% CI −0.29, −0.10), triglycerides (−0.13 mmol L −1, 95% CI −0.22, −0.03), fasting plasma glucose (−0.32 mmol L −1, 95% CI −0.43, −0.22) and haemoglobin A1c(−0.40%, 95% CI −0.52, −0.28) over 6–12 months. Significant changes remained after 2 years for several risk factors. Similar results were seen in sub‐group analyses. Interventions that cause weight loss are effective at improving cardiovascular risk factors at least for 2 years. © 2016 World Obesity